2010
DOI: 10.1289/ehp.0901731
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pesticide Exposure and Cancer Incidence in the Agricultural Health Study Cohort

Abstract: ObjectiveWe reviewed epidemiologic evidence related to occupational pesticide exposures and cancer incidence in the Agricultural Health Study (AHS) cohort.Data sourcesStudies were identified from the AHS publication list available at http://aghealth.nci.nih.gov as well as through a Medline/PubMed database search in March 2009. We also examined citation lists. Findings related to lifetime-days and/or intensity-weighted lifetime-days of pesticide use are the primary focus of this review, because these measures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(103 citation statements)
references
References 89 publications
0
95
0
2
Order By: Relevance
“…Une étude s'intéressant à de nombreuses expositions professionnelles a montré qu'une exposition aux pesticides était associée à la survenue de CCB, mais seulement si elle était très importante ; cette étude ne précisait pas les types de pesticides incriminés [17]. L'exposition aux pesticides a été mise en cause dans d'autres cancers, comme le cancer de la prostate et le cancer du sein où ces pesticides interviendraient notamment en perturbant les mécanismes endocriniens ; il y a peu d'études sur le sujet et les résultats sont contradictoires [54].…”
Section: Discussionunclassified
“…Une étude s'intéressant à de nombreuses expositions professionnelles a montré qu'une exposition aux pesticides était associée à la survenue de CCB, mais seulement si elle était très importante ; cette étude ne précisait pas les types de pesticides incriminés [17]. L'exposition aux pesticides a été mise en cause dans d'autres cancers, comme le cancer de la prostate et le cancer du sein où ces pesticides interviendraient notamment en perturbant les mécanismes endocriniens ; il y a peu d'études sur le sujet et les résultats sont contradictoires [54].…”
Section: Discussionunclassified
“…35,36 Additional support for a causal link between pesticide exposure and childhood leukemia comes from adult studies, such as the Agricultural Health Study, a prospective cohort of pesticide applicators, reporting increased risks of hematopoietic tumors, including leukemia, with 12 agricultural pesticides registered in the United States/Canada. 37 Preliminary Agricultural Health Study analyses also suggested an overall increase of cancers in the offspring of fathers exposed to 3 out of the 16 pesticides evaluated, an observation that will be important to reproduce. 38 Several pesticides commonly used in and around residences have been classified as possible human carcinogens (eg, tetramethrin, piperonyl butoxide, trifluralin) or probable/likely human carcinogens (eg, propoxur, permethrin, carbaryl).…”
Section: Pesticidesmentioning
confidence: 97%
“…1,3 Toxic effects on humans, such as acute neurological toxicity, impairment of neurological development, possible dysfunction of the immune, reproductive and endocrine systems, cancers, chronic kidney disease and other potential diseases have been reported in many papers. 4,5 PPCPs are used to prevent or treat human and animal diseases or to improve the quality of daily life. They have emerged as a major group of environmental pollutants over the past decades since some of them are produced and used in large quantities.…”
Section: Introductionmentioning
confidence: 99%